Personality and Healthy Lifestyles in Students of a University Corporation (Cuidado y Ocupación Humana, 2024)
This study analyzes the relationship between personality variables and quality of life among university students at the regional center in Cúcuta of the parte del centro regional Cúcuta de una Corporación Universitaria, considering the city's context as a border region. It is based on Eysenck's PEN model, which includes three personality dimensions: neuroticism, extraversion, and psychoticism, and incorporates Gray's contributions on behavioral activation and inhibition. A correlational approach with multivariate statistical analysis and logistic regression was applied to a sample of 360 students from various academic programs. The results reveal high levels of anxiety, impulsivity, and emotional instability, as well as denial of personal traits, especially in the neuroticism and psychoticism dimensions. Despite this, students perceive themselves as having a normal lifestyle, adapted to the challenges of the region. Their environment—characterized by poverty, informal labor, and violence—directly affects their psychological well- being and health behaviors. Nonetheless, the student population demonstrates resilience and adaptability, maintaining healthy lifestyles through academic and personal activities aimed at improving their quality of life. The findings show a clear relationship between personality traits, social context, and perceived well- being. This suggests that, despite adversity, these individuals manage to balance emotional and social demands with a positive attitude toward personal and professional development.
Keywords: Personality variables; quality of life; lifestyles